Pengaruh Jenis Asam dan Lama Marinasi Terhadap Karakteristik Sensoris, Mikrobiologis, dan Kimia Naniura Ikan Nila (Oreochromis Niloticus) - Okta Julvin Tarigan; Susi Lestari; Indah Widiastuti (Universitas Sriwijaya, 2016)
The purpose of this research was to investigate the sensory, microbiological and chemical characteristics of naniura tilapia (Oreochromis niloticus) with different types of acid and marinade time. The research was conducted on May until October 2015. This research used a Factorial Randomized Block Design (FRBD) two factors, the type of acid factor (Jungga citrus, lime, and citric acid) and marinade time factor (3 hours and 5 hours). Each treatments was replicated three times. The attributes observed were sensory test, pH, water content, and microbiological/TPC. Proximate and amino acid analysis will be done for all 3 hours marinade treatment. The results of organoleptic test showed that treatment of acid type and marinade time did not significantly affect the appearance and meat consisten but significantly affect on taste and aroma. The results of analysis TPC Jungga citrus treatment with lime showed the same value. While the value of TPC citric acid was higher but still safe for consumption. The results of proximate analysis for the three types of acid showed that Jungga citrus is the best nutrient content that the water content 63.25%, ash content 3.46%; 7.40% fat content, protein content 25.90% and carbohydrate 0.98 %. Analysis of the amino acid profile in naniura produced 17 amino acids, 9 essential amino acids and 8 non-essential amino acids